We are given with:
![{\quad \qquad \longrightarrow \sin (z)={\sf a}\:,\:z\in \mathbb{C}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qy23pa7curd9ibi4uzdh101xxpegbp36x0.png)
Recall the identity what we have for the sine function of complex numbers
Put the values to thus obtain:
![{:\implies \quad \sf (e^(\iota z)-e^(-\iota z))/(2\iota)=a}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ei7ylg01pq337d65imppnm0xq4ebkn87as.png)
![{:\implies \quad \sf e^(\iota z)-e^(-\iota z)=2a\iota}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3ohbykm1d5jqpc9xru9349rja3mhp77wgn.png)
Multiply both sides by
![{\sf e^(\iota z)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/m5xbhgjcz35xj0yi4f2kcedflml1hdo9xh.png)
![{:\implies \quad \sf e^(\iota z)\cdot e^(\iota z)-e^(-\iota z)\cdot e^(\iota z)=2a\iota e^(\iota z)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xm6olcgi1e49efmbxgb865rya7lhzzwggs.png)
![{:\implies \quad \sf (e^(\iota z))^(2)-2a\iota e^(\iota z)-1=0}](https://img.qammunity.org/2023/formulas/mathematics/high-school/wjxc593ri0zgzt6gyqegnebkv0elsndzj0.png)
Put x =
:
![{:\implies \quad \sf x^(2)-2a\iota x-1=0}](https://img.qammunity.org/2023/formulas/mathematics/high-school/m02r4w9zbob2nf3kmgskwq3otv7lm8botz.png)
Find the discriminant, here D will be, D = (-2ai)² - 4 × 1 × (-1) = 4 - 4a² = 4(1-a²)
Now, By quadratic formula:
![{:\implies \quad \sf x=\frac{-(-2a\iota)\pm \sqrt{4(1-a^(2))}}{2}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/qa96uv4vz3igq7qylw4dk01ovuw456uu0c.png)
![{:\implies \quad \sf x=\frac{a\iota \pm \sqrt{1-a^(2)}}{2}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7phpc0gzp1b6nhjxagqr5dmqk51kx2qucu.png)
![{:\implies \quad \sf e^(\iota z)=\frac{a\iota \pm \sqrt{1-a^(2)}}{2}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/41ok4rs892vyhilwqly50vptbzeub4yini.png)
![{:\implies \quad \sf \iota z=log\bigg(\frac{a\iota \pm \sqrt{1-a^(2)}}{2}\bigg)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/iyq8qd0y6gfw2am0yn8tqxq6ukarehs2w8.png)
Using the formula for logarithms, we have:
![{:\implies \quad \sf \iota z=log(a\iota \pm \sqrt{1-a^(2)})-log(2)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/w218hqdzenn2afb7hzmg9g2gyxtb2llhmv.png)
![{:\implies \quad \sf z=(1)/(\iota)log(a\iota \pm \sqrt{1-a^(2)})-(1)/(\iota)log(2)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/jkauqljudadwvfomrq8x1ur2gaq04lh7nn.png)
The sine function is periodic on 2πn and zero on (π/2), and the logarithmic expression becomes undefined for all ia±√(1-a²) < 0, so we will take modulus of it
![{:\implies \quad \boxed{\bf{z=(1)/(\iota)log\bigg|a\iota \pm \sqrt{1-a^(2)}\bigg|-(1)/(\iota)log(2)+(\pi)/(2)+2\pi n\:\:\forall \:n\in \mathbb{Z}}}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/gdid2v41dl0pyzya98x28yfg3akrqd6w22.png)